Assessment of health-related quality of life and its contributing factors using the WHOQOL-BREF questionnaire in patients with chronic liver disease - Manjacheri Kuppadakath Sagara, Vineesha Gangadharan, Ranjith Sristhi, Bipin Shaji, Adithi Kellarai, Juno Jerold Joel (Journal of Applied Pharmaceutical Science, 2023)
Chronic liver disease (CLD) is a serious condition characterized by a progressive decline in liver functions, which leads to impaired quality of life (QOL). A prospective cross-sectional study was conducted with 165 patients to identify the health-related QOL in CLD, for 6 months. The QOL of CLD patients was assessed using the World Health Organization quality of life-BREF questionnaire and the severity of the disease was assessed using Child-Pugh Model for End-Stage Liver Disease (MELD) score. The incidence of CLD was found to be high in males (89.09%). While assessing, the overall QOL was identified as 50.96 ± 15.77. The highest score was observed in the social relationships domain (58.33 ± 19.34) followed by environment (54.74 ± 16.74), psychological (46.70 ± 19.81), and physical health (44.08 ± 18.64). The socio-demographic factors associated with QOL include body mass index, education, alcohol consumption, smoking, and tobacco. In the Child-Pugh MELD Score, the QOL was higher in class A (Good hepatic function) with a MELD score of 6–9 (1.9% mortality), the mean score being 60 ± 21 in contrast with the other classes. From the study, it is evident that CLD has a significant impact on the QOL. Patient-centric collaborative care, including physicians, nurses, pharmacists, and other health care providers are essential to improve the QOL.